The Use of the Isdiman Ambarawa Museum as a Learning Resource - Dratiarawati, Aninda (Universitas Negeri Semarang, 2018)
This study aims to prove the existence of differences in student interest between classes that utilize the Isdiman Museum Ambarawa as a learning resource and those that do not. This research employs a quantitative approach with an experimental design to assess these differences. The population targeted in this study consists of eleventh-grade students at a high school in Ambarawa. The samples for this study were selected using a simple random sampling technique, adhering to a pretest-posttest control group design. Specifically, the sample includes eleventh-grade students from the social sciences track, with one group as the control class and another as the experimental class. The control class did not use the Isdiman Museum Ambarawa as a learning resource, while the experimental class integrated visits and activities at the museum into their curriculum. The objective is to measure any significant variations in student interest and engagement between these two groups, thus providing insights into the effectiveness of incorporating museum resources into traditional educational settings.